2017
DOI: 10.18483/ijsci.1176
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Forest Resources Dependency for local livelihood around Protected Area: A Case Study in Popa Mountain Park, Central Myanmar

Abstract: About: Forest resources play a crucial role for many livelihoods in the rural areas in Myanmar. Households in rural area of Myanmar, especially destitute households, depend on the forest related activities as one of the income diversification activities. This study estimated forest dependency and identified factors influencing dependency for households living around the Popa Mountain Park (PMP) in Myanmar. A sample of 75 households was randomly selected from three villages surrounding the Popa Mountain Park to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Young people also have multiple uses for forest products (Lepetu, Alavalapati, and Nair 2009). This finding is consistent with studies from Adam and EL Tayeb (2014), Chhetri et al (2013), Fonta and Ayuk (2013), Htun, Wen, &Ko Ko (2017), andLepetu, Alavalapati, andNair (2009). However, the finding contrasts with Ofoegbu (2017) and Baiyegunhi et al (2016), whose result indicates that older people are more likely to depend on forest resources than their younger counterparts.…”
Section: Socioeconomic Factors Influencing Forest Dependencysupporting
confidence: 92%
See 1 more Smart Citation
“…Young people also have multiple uses for forest products (Lepetu, Alavalapati, and Nair 2009). This finding is consistent with studies from Adam and EL Tayeb (2014), Chhetri et al (2013), Fonta and Ayuk (2013), Htun, Wen, &Ko Ko (2017), andLepetu, Alavalapati, andNair (2009). However, the finding contrasts with Ofoegbu (2017) and Baiyegunhi et al (2016), whose result indicates that older people are more likely to depend on forest resources than their younger counterparts.…”
Section: Socioeconomic Factors Influencing Forest Dependencysupporting
confidence: 92%
“…Using the forest dependency literature as a guide, the socioeconomic conditions of households affect their reliance on forest resources. This study reviews existing studies (see, for example, Adam and EL Tayeb, 2014;Baiyegunhi et al, 2016;Chhetri et al, 2013;Fonta & Ayuk, 2013;Lepetu, Alavalapati, and Nair, 2009;Ntiyakunze & Stage, 2021;Htun, Wen, & Ko Ko, 2017;Mujawamariya & Karimov, 2014;Garekae, Thakadu, and Lepetu, 2017;Ofoegbu, 2017;and Ntiyakunze and Stage, 2022) who contributed significantly to investigating socioeconomic factors influencing forest dependability. However, the variation in these findings underscores the need for additional research to critically examine the influence of socioeconomic factors on forest dependence.…”
Section: Socioeconomic Factors Influencing Forest Dependencymentioning
confidence: 99%
“…This is within the values reported in previous studies. For example, forest income dependency was reported in protected areas in Myanmar: 38.8% for three villages surrounding the Popa Mountain Park by Htun et al [23] and around 50% for two villages around Natma Taung National Park by Aung et al [11]. The forest dependency values in villages near the production forests in Bago Yoma region, Myanmar, which is the same region as this present study, were also reported to be 25% in 10 villages in both western and eastern aspects of Bago Yoma region by Khaine et al [24], and 37% in the Taungoo District by Soe and Yeo-Chang [25].…”
Section: Forest Cash Income Dependencymentioning
confidence: 99%
“…Dependency on forest and other associated resources as the primary energy source were very high, especially in the rural areas of the developing countries (Hussain et al 2019). As for example, the dependency on forest biomass as primary source of energy was up to 87% in India (Madhu 2009, and Bhatt et al 2016), 77% in Nepal (Benato et al 2016), 78% in Bhutan (Rana et al 2016), 73% in Bangladesh (Huda et al 2014), 38.82% in Myanmar (Wen et al, 2017), 30% in Malawi (Fisher, 2004); up to 39% in western Ethiopia (Mamo et al, 2007); 40% in Zimbabwe (Cavendish, 2000) and up to 80% in Sub Saharan Africa (Sassen et al 2015). Fuelwood extraction often leads to forest degradation when the extraction is high, forest resources are limited, and alternative energy resources such as kerosene or Liquid Petroleum Gas (LPG) are unavailable (Kohl et al 2015, Specht et al 2015, WEC 2016, Nagothu 2001).…”
Section: Introductionmentioning
confidence: 99%